Oxford international primary english student book for grade 4 - Danihel, Emma (Karachi: Oxfor University Press., 2022)
The Oxford International Primary English: Student Book for Grade 4 focuses on strengthening the language skills of young learners by providing a rich variety of texts and interactive activities. It aims to deepen students$1 (Bunderstanding of reading, writing, grammar, and vocabulary through structured lessons. The book encourages critical thinking and creative expression by engaging students with both fiction and non-fiction content, including stories, reports, and poetry. Additionally, it emphasizes skills like summarizing, analyzing characters, and improving sentence structure. With a global approach, the book helps students develop communication skills that are applicable across cultures, fostering a love for language and literature.s